An Understanding-based Study between Traditional Chinese Classroom Teaching and PAD Classroom Teaching in Chinese University Students’ College English Classes - Su, Huanan (JET (Journal of English Teaching), 2023)
The current study intended to have a brief understanding-based analysis of the Chinese university students’ understanding of the traditional Chinese classroom teaching method and the PAD classroom teaching method so as to investigate the feasibility and efficiency of the two teaching methods in the Chinese university students’ College English classes. Through applying a quantitative research design using the descriptive approach, questionnaires were distributed to thirty Chinese university students. The current study had revealed that the PAD classroom teaching method was much more favorable than traditional Chinese classroom teaching method by most of the Chinese university students in their College English classes. Thus, the implication of the current study was that the PAD classroom teaching method was strongly suggested to be given more opportunities to be applied and practiced by the teachers in the Chinese university students’ College English classes.